A COMPARATIVE MOVE ANALYSIS OF INTER-DISCIPLINARY RESEARCH ARTICLES WRITTEN BY REPUTABLE INDONESIAN AUTHORS THROUGHOUT THEIR EARLY-CAREER PERIOD - Athirah Jihan Khairani; Eri Kurniawan; Arif Husein Lubis (University of Kuningan, 2023)
Publishing scientific papers, particularly research articles (RAs), has become a requirement and essential component for academics’ life. As a result, there is a growing need for academics to produce research articles for international publications. However, many writers, especially novice and inexperienced ones, still struggle to achieve this goal because they fail to adhere to the accepted conventions. This study attempts to look into the rhetorical moves in full-length English RAs written by reputable Indonesian lecturers from the hard and soft sciences disciplines in the early stage of their careers. This study employed a modified framework of analysis proposed by Maswana et al. in 2015. The findings showed that, in general, the papers’ rhetorical structures from abstract to conclusion were quite comparable, reflecting the universal writing rules of a research paper. However, the striking difference lies in the method section, specifically the absence of Move 5 in all soft sciences articles. This may be due to disciplinary conventions. The findings of the study may offer insightful instructional material that can assist students or researchers in honing their academic writing abilities.Keywords: early-career; full-length English RAs; hard sciences; move analysis; rhetorical structure; soft sciences.